EFEKTIFITAS MODEL PEMBELAJARAN PBL UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MEMECAHKAN MASALAH - Ahmadi (AGHNIYA: Jurnal Perbankan Syari'ah, 2019)
This paper attempts to find out how effective the Problem Based Learning (PBL) learning model is in improving the ability of Class After analyzing the results of the research conducted, it can be seen that the application of the PBL learning model in the Ushul Fiqh subject is for class are more likely to try to find their identity which can increase students' activeness and increase their ability to solve problems, and by using the problem based learning model it shows that 90% of all students tend to be more active in carrying out activities in class 11 Religious 1 and 2. learning and become more able to solve every problem faced and the remaining 10% are less active and have not been able to solve the problems given by the teacher.